Sleep and circadian difficulties in schizophrenia: presentations, understanding, and treatment - Freeman, D; Waite, F (Cambridge University Press, 2025)
It is common in mental health care to ask about people’s days but comparatively rare to ask about their nights. Most patients diagnosed with schizophrenia struggle at nighttime. The next-day effects can include a worsening of psychotic experiences, affective disturbances, and inactivity, which in turn affect the next night’s sleep. Objective and subjective cognitive abilities may be affected too. Patients commonly experience a mix of sleep difficulties in a night and across a week. These difficulties include trouble falling asleep, staying asleep, or sleeping at all; nightmares and other awakenings; poor-quality sleep; oversleeping; tiredness; sleeping at the wrong times; and problems establishing a regular sleep pattern. The patient group is also more vulnerable to obstructive sleep apnea and restless legs syndrome. We describe in this article how the complex presentation of non-respiratory sleep difficulties arises from variation across five factors: timing, mental state, need for sleep, self-care, and environment. We set out 10 illustrative patterns of such difficulties experienced by patients with non-affective psychosis. These sleep problems are eminently treatable with intensive psychological therapy delivered over approximately eight sessions. We describe key techniques and their typical order of implementation by presentation. Sleep problems are an important issue for patients. Giving them the therapeutic attention patients often desire brings both real clinical benefits and improves views of services. Treatment is also very likely to lessen psychotic experiences and mood disturbances while improving daytime functioning and quality of life. Tackling sleep difficulties can be a route toward the successful treatment of psychosis.